A short guide to fraud risk : fraud resistance and detection - Samociuk, Martin; Doody, Helenne; Iyer, Nigel K. (Short guides to business risk, 2010)
"The book gives a concise but thorough introduction to the risk of fraud based on a six-element strategy. It includes practical steps to assess and treat fraud risks across an organisation, including those relating to executive directors. It also provides practical steps to develop fraud awareness across an organisation and how to implement an effective fraud detection and incident management program." "The application of the principles is illustrated with example documents and numerous case studies aimed at assisting the reader to implement either individual elements or a complete fraud risk management strategy."--Jacket